HUBUNGAN FUNGSI KEPEMIMPINAN KEPALA DESA DENGAN EFEKTIVITAS KERJA APARATUR PEMERINTAH DESA (Suatu Studi Di Kecamatan Langowan Utara Kabupaten Minahasa) - Rewah, Daniel; Lengkong, florence Daicy; Mandey, Jantje (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: This study aims to: Describe the function of the leadership of the village head and villageofficials effectiveness; and analyze the relationship between the leadership function of the villagehead and village officials work effectiveness in Minahasa District of Northern Langowan. Purposivesample of respondents assigned as many as 80 people were distributed into four (4) of 8 (eight)villages in the districts of North Minahasa Langowan. Members randomly drawn sample consisted of40 people from local government and 40 others are members of BPD, community / religion. Themethods and approach used in this research is descriptive and quantitative approach by applyinganalytical techniques percentage, product moment correlation and simple linear regression. Theresults obtained from this study are: the results of the analysis of frequency table shows that theleadership function village head seen from the dimensions of the initiative and dimensions ofgovernment communications, overall in the category "medium" or intermediate, while theeffectiveness of village officials, especially in District Langowan North is at "high". Chi-square testresults showed that the relationship between the function of leadership effectiveness village withvillage officials in the District of North Langowan "significant" at the 95% confidence level. Thuswe can conclude that if the village head execute leadership functions properly, it will boost theeffectiveness of village officials themselves. This study gives some suggestions, among others: thatthe Head of the village in the exercise of its functions have always sought to do the initiation of thedevelopment programs that require leadership initiatives, as well as establishing two-waycommunication so that village officials feel comfortable so motivated to improve the effectiveness oftheir work.Keywords: Function of Leadership, Effectiveness village officials work.